Gender Inequality and Media Representation: A Critical Discourse Analysis of Femicide Coverage in Indonesia - Nahdliyah, Nur Laili; Robot, Marselus (Journal of Pragmatics and Discourse Research, 2024)
Femicide, recognized by the UN as the killing of women based on honor, sexual orientation, or gender identity, is a severe manifestation of gender inequality and sex-based violence. Often linked to domestic violence, sexual harassment, and ongoing trauma, femicide represents one of the most extreme forms of violence against women. In 2023, 159 cases of femicide in Indonesia were reported, with most committed by intimate partners (Komnas Perempuan). This study examines how femicide cases were reported by three major Indonesian online media outlets—Kompas.com, Republika.co.id, and Tirto.id—analyzing nine news articles focused on harassment, domestic violence, and murder. Using Sara Mills' critical discourse analysis (CDA), the research explores how these media portray gender injustice against women. The findings reveal that women are consistently depicted as weak and powerless, trapped in a patriarchal culture that normalizes violence against them. This portrayal reinforces gender stereotypes, weakening legal responses and perpetuating male dominance. The study underscores the need for more balanced and empowering media representations of women to challenge the deep-rooted gender inequalities in society.